Pengaruh Kelekatan Ayah Terhadap Gejala Depresi Remaja Perempuan Di Kota Bandung - Jannah Yuniar; Indri Utami Sumaryanti (Jurnal Psikohumanika, 2020)
Abstract The purpose of this study was to examine the effect of father-daughter attachment towards adolescent depressive symptoms in Bandung. The sampling technique in this study was purposive sampling with a questionnaire data collection method. The instruments used in this study were the Inventory of Parent And Peer Attachment (IPPA) and Beck Depression Inventory (BDI). The sample in this study were 64 teenage girls in Bandung aged 15-24 years who have experienced three symptoms of depression for at least 2 weeks. The simple linear regression test results show that the higher the father attachment, the lower the depressive symptoms of female adolescents in Bandung. However, the magnitude of this influence is only 13.9%. For future researchers who are interested in investigating further about this variable, it is suggested to include control variables that can contribute to depressive symptoms, such as self-esteem, self-concept, self-efficacy, attributional style, and social support.